A man with polycythemia vera, myelodysplastic syndrome and acquired microcytosis. Issue 8 (13th August 2019) - Mann, Michael; Kreuzbauer, Tania; Sykes, David B
Abstract : A 59-year-old white man with known myeloproliferative neoplasm (MPN) and myelodysplastic syndrome (MDS) presented with worsening leucocytosis and thrombocytosis in the setting of a presumed infection. The patient had been diagnosed 2 years earlier with an MPN/MDS overlap syndrome, based on characteristic mutations in JAK2, IDH1 and SRSF2. During his current evaluation, he was noted to have new microcytosis, with a mean corpuscular volume of ~70 fL down from his baseline of ~90 fL. His laboratory workup showed normal iron studies, normal haemoglobin electrophoresis, and no evidence of haemoglobin H or mutations in his ATRX coding region. Without any identifiable cause of his new microcytosis, he was given a presumptive diagnosis of acquired thalassemia in the setting of his unusual MPN/MDS overlap syndrome.